(untitled) (Revista de Investigaciones Universidad del Quindío, 2022)
Technological development has resulted in the communication of different signs throughout the history of human beings. Undoubtedly, the most significant moment took place in modernity, when it established a decisive rupture with the object, placing it as the product of reason thought by the subject. We are certain that this change has been reflected in the interior, intentionality and identity of the latter. In this order of ideas, the problem detected in this article is the way in which the object disappears within virtual processes and is replaced by language immersed in interpretations that lead to the generation of a meta-informational process flooded with anonymity and uncertainty, a situation that impacts on the construction of the subject’s identity. It is detected that within these meta-informational processes, the subject is tied to the representation and establishes a cyclical dynamic that projects his identity, resulting in a process of submission to the sign that the same individual has codified through his interests and the way he approaches his reality. This paper explores this process of submission, using the metaphor of Ixion and Nefele, which adequately describes the behavior of the meta-informational identity.